Participant Reported Improvement in Cellulite by Vari-Pad Apparel and Objective Measurements – A “First Use” Pilot Study - Kiely MJ; Poulsen A; Muschamp SD; Sallis C; Whiteley MS (Dove Medical Press, 2023)
Melissa J Kiely, Ashleigh Poulsen, Simon D Muschamp, Chloe Sallis, Mark S Whiteley Research Department, the Whiteley Clinic, Guildford, Surrey, UKCorrespondence: Mark S Whiteley, The Whiteley Clinic, 1 Stirling House, Stirling Road, Guildford, Surrey, GU2 7RF, UK, Email mark@thewhiteleyclinic.co.ukBackground: Cellulite affects 80- 90% of post-pubertal females and, although cosmetic, has proven adverse psychological effects. A new compression garment with patented "vari-pad" technology has been developed, aiming to stimulate lymphatic return from the buttocks and thighs. The primary aim of this small pilot study was to assess participant satisfaction after using this garment in the short term and secondarily, to look for any objective improvements.Methods: Eighteen female participants (mean 47.5y, range 26- 60) completed the study. There were 2 weeks of "stabilisation", 4 weeks of wearing the garment, and 2 weeks of further assessment. With the initial assessment, there were 9 visits for each participant. At each visit, weight, participant satisfaction (0- 10), 3D images (Canfield, USA) and transcutaneous water content (LymphScanner, Delfin Technologies, Finland) and comfort (0- 10) were recorded.Results: There was no significant weight change in any of the participants during the trial period. After 4 weeks of wearing the garment, there was a significant improvement in participant satisfaction of their cellulite (n = 15, p = 0.0036) with a mean improvement of 18.5%. 3D image analysis of dimple volume showed no significant change in buttock cellulite, a significant decrease in left thigh cellulite (n = 17, p = 0.0123), but not on the right (n = 14, p = 0.6890). There was a significant decrease of localised water (n = 36, p = 0.0041). Comfort was 86% (range 40- 100%) and there were no adverse reactions to the garment.Conclusion: The vari-padded compression garment produced a significant improvement in participant satisfaction after just 4 weeks of treatment. Objective measurements failed to show a significant difference in cellulite on the buttocks but showed a significant improvement in the thighs by analysis of both dimple volumes and reduced transcutaneous water measurements. Further study is suggested to demonstrate if longer timeframes for use of the apparel will lead to further significant improvement in the appearance of cellulite.NCT Number: NCT05748678.Keywords: cellulite, compression, garment, hosiery